Whole-genome resequencing reveals genetic diversity and adaptive evolution in Chinese honeybee (Apis cerana cerana) in Guizhou, China - Wang, Yinchen; Zeng, Bing; Deng, Mengqing; Zhao, Tian; Liao, Yan; Ren, Rongqing; Wang, Hua; Yuan, Yang (Frontiers in Genetics, 2024)
Introduction: Guizhou Province, characterized by complex and diverse geographic and climatic environments, has rich genetic resources for the Chinese honeybee (Apis cerana cerana) and is one of the main bee-producing areas in China. However, research on the genetic diversity of Chinese honeybee in the Guizhou region is very limited, despite implications for conservation of biodiversity. Methods: In this study, we analyzed the genetic diversity, differentiation, and selection signals based on 116 Chinese honeybees from 12 regions in Guizhou Province using whole-genome sequencing. Results: We identified 1,400,430 high-quality SNPs across all samples. A population structure analysis revealed two independent genetic subgroups of Chinese honeybees in Guizhou, a Yunnan-Guizhou Plateau population in western Guizhou and a hilly-mountainous population in eastern Guizhou. The average nucleotide diversity (Pi) ranged from 0.00138 to 0.00161 and average expected heterozygosity (He) ranged from 0.2592 to 0.2604. The average genetic differentiation index (FST) for Chinese honeybees in pairwise comparisons of 12 regions ranged from 0.0094 to 0.0293. There was clear genetic differentiation between the western plateau and the eastern hilly mountainous areas of Guizhou; however, FST values between the eastern and western populations ranged from 0.0170 to 0.0293, indicating a low degree of differentiation. A genome-wide scan revealed a number of genes under selection in the Yunnan-Guizhou Plateau environment. These genes were related to growth and development, reproduction, and cold resistance, and several candidate genes involved in environmental adaptation were identified, including CTR, MAPK, MAST, HSF, and MKKK. Discussion: The results of the present study provide important theoretical bases for the conservation, evaluation, development, and utilization of genetic resources for Chinese honeybees in the Guizhou region and for further investigations of environmental adaptation and underlying mechanisms in the species.